(3GdLGeY aj GdTQM (B( (3TQM GdJMQjQ(B)s - (3CHh GdMSjf RjO Hf eMeOs ((3eMeO Hf efUhQ Hf SdjeGf s)
(3ChdgG (B:s
(3HOC HHGH GdhdGA Hbhdg (B: (3eSCdI , hGdhdGA VQHGf hdGYJb hdG ehGdGI , hgj ESdGe GdMQHi Ydi jOi eSde s
(3BNQgG (B:s
(3GdYbO UMjM hGdTQW jaSO , hNQL GHf TQjM hLgkG BNQ eKd gPG , hGdMeO ddg hMOg Je GdLRA GdSGHY s
(3GdLRA GdSGHY ef KeGfjI CLRGAs
(3GdfSNI YdjgG bQGAI hSeGY SfI (B738 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3abg GdePGgH GdCNQis